Inhibition of mRNA export in vertebrate cells by nuclear export signal conjugates - Pasquinelli, Amy E. (The National Academy of Sciences of the USA, 1997)
Leucine-rich nuclear export signals (NESs) are recognized by the NES receptor exportin 1 and are central to the export of multiple shuttling proteins and RNAs. The export of messenger RNA in vertebrates was, however, thought to occur by a different pathway, because inhibition by injection of a synthetic Rev NES conjugate could not be demonstrated. Here we find that peptide conjugates composed of the NES of either protein kinase A inhibitor protein (PKI) or the HIV-1 Rev protein, when coupled to human serum albumin, are potent inhibitors of mRNA and small nuclear RNA export. These results provide direct evidence that mRNA export in vertebrates depends on interactions between an NES and its cognate NES receptors. PKI NES conjugates are significantly more efficient at inhibiting RNA export than are REV NES conjugates, indicating that different NESs may have different abilities to promote protein and RNA export. Surprisingly, an expected control conjugate containing the mutant Rev NES sequence M10 strongly inhibited the export of intronless dihydrofolate reductase mRNA. Nuclear injection of NES peptide conjugates led to mislocalization to the nucleus of 10–20% of the cytoplasmic Ran GTPase-binding protein (RanBP1) indicating that RanBP1 shuttles between the nucleus and the cytoplasm via an NES pathway. These results demonstrate that in vertebrates the export of mRNA, like that of small nuclear RNA, 5S rRNA, and transport factors such as RanBP1, employs NES-mediated molecular machinery.